Effect of Varying Dietary Lipid Levels and Protein to Energy (P:E) Ratios on Growth Performance, Feed Utilization and Body Composition of Sub-adult Silver Pomfrets, Pampus argenteus (Euphrasen, 1788) - Hossain, M. Arshad; Almatar, Sulaiman M.; James, Charles M. (Pakistan Journal of Nutrition, 2011)
This study investigated the effect of varying levels of lipid and protein to energy (P:E) ratios on growth and feed utilization and body composition of sub-adult silver pomfret (Pampus argenteus). Duplicate groups of fish (average weight 98.2±0.2 g) were fed for 8 weeks three iso-nitrogenous experimental diets (49% protein) containing 12, 16 and 20% crude lipids with corresponding P:E ratio of 23.66, 22.62 and 21.60 for diets 1, 2 and 3 respectively. Mean body weight gain and specific growth rates of fish fed 16% and 20% lipid diets were significantly higher than that of 12% lipid diets. Daily feed intake was not affected by the dietary lipid levels, but there were significant differences in feed conversion ratio, protein efficiency ratio, apparent net protein utilization, energy and lipid retention values. Proximate analysis indicated that the lipid and fatty acid composition of whole body were affected by diets. Whole body of fish fed 16 and 20% lipid diets showed significantly (p